Pelatihan Pemanfaatan Fitur Instagram Story Untuk Meningkatkan Customer Engagement pada Startup - Dhanar Intan Surya Saputra; Al Hafidz Hanifan Islahi; Agung David Pamungkas; Hellik Hermawan (Yayasan Literasi Sains Indonesia, 2022)
The Startup is a newly formed business that was established from a problem that arose in the community and is expected to be able to solve and deal with this problem. The Prestasi Kita Bersama as a Startup with its innovative products in the field of Education. Currently, this Startup is gaining the community's trust. In carrying out its business model, many use Instagram @prestasikita. Therefore, to maximize the use of Instagram, Startup management needs to manage and explore all the features available on Instagram. This is important to do to attract potential customers' interest and increase customer engagement. Based on these problems, it is necessary to provide training and assistance for startups, especially using the Instagram Story feature to increase customer engagement. During the training, the parts for using, creating and editing content, including Highlights, Poll stickers, Emoji slider stickers, Questions, Quizzes, Chat stickers, Product stickers, Countdown, and Instagram Shopping. The enthusiasm of partners as participants in a series of training activities is very high so that it can run smoothly until it is finished without any obstacles or obstacles. The hope is that in the future, the use of Instagram Stories can be maximized by partners.